A qualitative study of work motivation among the media and creative workers in Malaysia - A Mohamad Isa, Siti Fariza; Yasin, Megat Al-Imran; Yinhua, Hao; Abdul Latif, Mohd Syaufiq (Secholian Publication, 2023)
The creative industry is a booming sector in the contribution to the gross domestic product in a country especially towards the gig economy. Among the pillars within the creative industry is those from the film and drama sectors. Terms such as above-the-line and below-the line are segregated to identify their nature of work and how it contributes to the audio-visual industry. Therefore, the creative industry practitioners are facing challenges in maintaining their status quo for better economic gains and protecting their well-fare due to the nature of the creative industries as freelancers. This studys objective is to understand the problems that are faced by the creative industry stakeholders in generating their income and also to study the possible effects of inefficiency of well-fare protection in Malaysia's creative industry. This study also uses qualitative study and thematic analysis to analyse the data gained from focus group discussion of five (5) participants where four (4) of them are creative creators and one (1) of them was from the legislative office of copyright protection in Malaysia. The interviews were recorded into audio files and transcribed verbatim. The data acquired were later on analysed using ATLAS.ti and have managed to discover three (3) emergent themes that reflects the whole purpose of the study. The impact of this study is to understand what could possibly be done to improvise the economic and welfare well-being of the creative industry practitioners.